PERAN INNOVATIVE WORK BEHAVIOUR (IWB) DAN PERCEIVED ORGANIZATIONAL SUPPORT (POS) DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL INTERVENING DALAM PENINGKATAN KINERJA KARYAWAN PADA UMKM COFFEESHOP DI SERANG - Pancasasti, Ranthy (Universitas Banten Jaya, 2023)
Background: MSMEs have an important role in the Indonesian economy, as a country with the largest number of MSMEs in ASEAN. MSMEs often face challenges in improving employee performance. Perceived Organizational Support and Innovative work behavior are factors that influence employee performance. Purpose: to broaden new understanding and perspectives regarding the impact of POS and IWB on employee performance through employee engagement variables, with the hope of forming a new research model. Novelty: in considering the role of IWB and POS with employee engagement as an intervening variable in improving employee performance at MSMEs coffee shops in Serang. The research methodology used: is a quantitative approach with a questionnaire as a data collection tool. The number of respondents is 50 samples, consisting of employees and coffee shop owners in the Serang area, Banten. The results showed: IWB and POS have a positive and significant impact on employee performance. However, employee engagement does not strengthen the effect of POS on employee performance. Keywords: Innovative work behavior, Perceived organizational support, Employee performance.